(untitled) (Progressive Agriculture, 2014)
Norin 10 based dwarfing genes (Rht1 and Rht2) have been widely exploited for increasing the grain yield in bread wheat (Triticum aestivum L.) by improving partitioning of assimilates to grain. Eight semi-dwarf wheat genotypes having either Rht1 or Rht2 dwarfing genes were compared with a tall control named, Kheri (rht) having no dwarfing genes were evaluated at Rajshahi University, Bangladesh for yield and yield contributing traits. Significant differences in grain yield and yield components were observed in genotypes under study showing the effects of dwarfing genes. Genotype Seri 82 (Rht1) and Kanchan (Rht2) had medium plant height of 75.73 and 72.22 cm respectively, highest number of tillers/plant (7.33 and 7.67), highest number of spikes/plant (6.33 and 6.67) resulted the highest grain yield per plant. Because the dwarfing genes not only provide lodging tolerance but also perhaps pleiotropically affected high yield by allowing more tillers to survive. Number of tillers/plant and number of spikes/plant showed very strong positive correlation with grain yield per plant in all the genotypes. Kheri (rht) with highest plant height (95.17cm) reduced number of tillers/plant (4.00) and spikes/plant (3.67) had the lowest grain yield per plant (3.85g). Aghrani possessed significantly the highest number of grains/spike with medium grain yield/plant (5.94g). The degree of relationship varied from genotype to genotype. DOI: http://dx.doi.org/10.3329/pa.v18i2.18075 Progress. Agric. 18(2): 49 - 55, 2007